Difficulties and features of the implementation of Agile-culture in the field of marketing on the example of a marketing digital-agency - Tsykanova, Zh. (International School of Economics KAZGUU, Nur-Sultan, 2022)
In a rapidly changing environment, companies need to react quickly to changes in the external environment, adapt to them, develop strong competitive advantages in order to succeed and take significant positions in the market. The external environment is changing rapidly, offering companies to survive in conditions of economic crisis, pandemic and other factors, causing the desire of management to apply new management methods to increase profits. In this study, an attempt was made to determine how the implementation of Agile culture can have an impact on increasing profits in the company, how it contributes to improving employee efficiency and improving work results. In particular, using the example of a marketing digital-agency, a study was conducted on whether the methods of Agile culture used affect the efficiency of employees, whether this culture is applicable in a non-traditional Agile field, what stages of change management need to be passed on the way to building this culture and what is their peculiarity. To test the hypothesis that during the implementation of Agile culture in a non-classical for Agile sphere, there will be more obstacles than in the classical one, anonymous surveys and in-depth interviews were conducted among employees of all departments of the agency. Respondents were asked to answer questions from an anonymous survey and an in-depth interview. The answers were analyzed with the output of the average value. The results showed that there is a similarity of the obstacles that companies face when implementing Agile culture in the classical sphere. The only obstacle is the human factor and the willingness to change. There was resistance in the process of implementing the changes, despite the young age of the agency's employees adaptation to the changes is relatively slow. These results show that obstacles in the form of resistance naturally occur on the way of implementing changes, regardless of whether it is a classic or not a classic area for Agile culture. Although it was assumed that young employees adapt to changes faster, it turned out that age does not matter. More important is the willingness to change and the developed skills of employees. Based on this, when implementing Agile culture, the level of developed skills, the quality of interpersonal communication and the gradual introduction of changes should be taken into account
Keywords: Agile-culture, Agile-culture in the field of marketing, digital-agency